Real wages over the business cycle: OECD evidence from the time and frequency domains - Julián Messina; Chiara Strozzi; Jarkko Turunen (Institute for the Study of Labor (IZA), 2008)
We study differences in the adjustment of aggregate real wages in the manufacturing sector over the business cycle across OECD countries, combining results from different data and dynamic methods. Summary measures of cyclicality show genuine cross-country heterogeneity even after controlling for the impact of data and methods. We find that more open economies and countries with stronger unions tend to have less pro-cyclical (or more counter-cyclical) wages. We also find a positive correlation between the cyclicality of real wages and employment, suggesting that policy complementarities may influence the adjustment of both quantities and prices in the labour market.
urn:nbn:de:101:1-20081217257
Keywords: E32; 330; Real wages; business cycle; dynamic correlation; labour market institutions; Reallohn; Konjunktur; Verarbeitendes Gewerbe; Korrelation; Arbeitsmarktflexibilisierung; Offene Volkswirtschaft; Beschäftigungseffekt; OECD-Staaten